Responses of grapevine genotypes to abiotic stress - N. G. Nilov; I. I. Ryff; S. P. Berezovskaya; V. Yu. Stamatidi; M. S. Popova; V. A. Volynkin; V. V. Llikhovskoi (Труды по прикладной ботанике, генетике и селекции)
Background. Salt stress reduces water supply and causes ionic imbalance in the plant, eventually leading to a decrease in plant growth, functional activity, and productivity. Variable salinity levels in the field make it difficult to select salt-tolerant cultivars, so a need for other testing methods arises.   Materials and methods. The plant material consisted of two own-rooted Vitis vinifera (L.) genotypes: cv. ‘Asma’, and hybrid M. No. 8-08-8-4 (‘Kok Pandas’ × ‘Zeibel 6357’). Salt stress was simulated by treating with NaCl at 0, 50, 80, 100, and 120 mM concentrations. Water status was measured by the leaf water potential (Ψ) using a pressure chamber. Changes in the leaf areaand total root length were assessed in vitro.   Results. Salt stress affected growth characteristics and yield structure of both own-rooted vines, but hybrid M. No. 8-08-8-4 was more sensitive. The hybrid showed greater yield reduction (38.6 %) than cv. ‘Asma’ (28.4 %), while the mass concentration of sugars was higher in ‘Asma’. The greatest differences in the predawn leaf water potential were observed for ‘Asma’ and M. No. 8-08-8-4 on the 45th day of irrigation with water containing different NaCl concentrations. The root length of the more salt-tolerant cultivar reduced in vitro to a greater extent.   Conclusion. The functional abilities of a cultivar depend on the level of salinization and the genotype. Cv. ‘Asma’ demonstrated higher salt tolerance compared to hybrid M. No. 8-08-8-4. Leaf water potentials characterizing the water status of plants were measured. The responses to salinization were the same in the vines grown in vivo and in vitro, so it is possible to perform testing for salt tolerance in vitro.